2001
DOI: 10.1016/s0925-4773(00)00540-2
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal dermis development depends on a signal from the dorsal neural tube, which can be substituted by Wnt-1

Abstract: To investigate the origin and nature of the signals responsible for specification of the dermatomal lineage, excised axial organs in 2-day-old chick embryos were replaced by grafts of the dorsal neural tube, or the ventral neural tube plus the notochord, or aggregates of cells engineered to produce Sonic hedgehog (Shh), Noggin, BMP-2, Wnt-1, or Wnt-3a. By E10, grafts of the ventral neural tube plus notochord or of cells producing Shh led to differentiation of cartilage and muscles, and an impaired dermis deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 65 publications
2
47
0
1
Order By: Relevance
“…3D,E). These data suggest defective development of derivatives from the dermomyotome, including dorsal dermis (Olivera-Martinez et al, 2001 and BAT (Atit et al, 2006). Consistently, hair follicles, whose development requires intimate interactions between epidermis and dermis (Schmidt-Ullrich and Paus, 2005), while normal in the flanks, exhibited significant reduction in number in the dorsum of Pnn 3f/3f embryos ( Fig.…”
Section: Pnn Hypomorphic Phenotypes Suggest Its Role In the Developmesupporting
confidence: 67%
See 2 more Smart Citations
“…3D,E). These data suggest defective development of derivatives from the dermomyotome, including dorsal dermis (Olivera-Martinez et al, 2001 and BAT (Atit et al, 2006). Consistently, hair follicles, whose development requires intimate interactions between epidermis and dermis (Schmidt-Ullrich and Paus, 2005), while normal in the flanks, exhibited significant reduction in number in the dorsum of Pnn 3f/3f embryos ( Fig.…”
Section: Pnn Hypomorphic Phenotypes Suggest Its Role In the Developmesupporting
confidence: 67%
“…Instead, Pnn hypomorphs exhibited a complex phenotype. Intriguingly, all of these phenotypes-vertebral patterning (Ikeya and Takada, 2001;Aulehla et al, 2003), dorsal dermis development (Olivera-Martinez et al, 2001, BAT formation (Atit et al, 2006), and palate and outflow tract development (Hamblet et al, 2002;Hutson and Kirby, 2003;Schmidt and Patel, 2005)-have been observed in mice having defects in Wnt/␤-catenin signaling. This finding raised an interesting possibility that PNN might be involved in the regulation of Wnt/␤-catenin signaling during mouse development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the role of molecules in these processes, cells secreting exogenous proteins can be implanted into embryonic tissues. One recent attempt showed that cells secreting Wnt-1 can mimic the dorsal neural tube and induce a feathered skin (Olivera-Martinez et al, 2001). In this study a Wnt-1 producing cell line was grafted to the embryos after removal of the neural tube and notochord.…”
Section: Mesenchymamentioning
confidence: 99%
“…Contrairement aux progéniteurs myogéniques, les cellules dermogéniques cessent rapidement d'exprimer les gènes Pax [8], migrent en direction de l'ectoderme et forment en dessous de ce dernier un mésenchyme qui exprimera le marqueur Dermo-1 [9]. Il a été montré que Wnt-1, qui est produit par la partie dorsale du tube neural, exerce une action inductrice du développement du derme dorsal [10]. Le dermomyotome produit également deux lignées endothéliales : les cellules endothéliales des vaisseaux sanguins (angioblastes) qui expriment VEGFR2 (vascular endothelial growth factor receptor-2), et les cellules endothéliales des vaisseaux lymphatiques (lymphangioblastes) [11].…”
Section: Le Dermomyotome Contribue à La Formation Du Derme Dorsal Et unclassified